Sinn + Sinnlichkeit : Körper + Geist im Bild. - Deecke, Thomas; Zech, Hanne; Neues Museum Weserburg Bremen (Bremen : Neues Museum Weserburg, 2000)
Byars, James Lee ; Bourgeois, Louise ; Beuys, Joseph ; Fautrier, Jean ; Fontana, Lucio ; Guiton, Jean-François ; Hatoum, Mona ; Irwin, Robert ; Kapoor, Anish ; Klein, Yves ; Kounellis, Jannis ; Lassnig, Maria ; Manzoni, Piero ; Martin, Agnes ; Morris, Robert ; Murakami, Tomoharu ; Neto, Ernesto ; Oursler, Tony ; Paolini, Giulio ; Rainer, Arnulf ; Ryman, Robert ; Solano, Susana ; Trockel, Rosemarie ; Twombly, Cy ; Wurm, Erwin ; Zaugg, Rémy
korte bibliog. per kunstenaar p. 136-140
Duits
Duits & Engels
Engels
Sinn + Sinnlichkeit : Körper + Geist im Bild, Neues Museum Weserburg, Bremen, 21.05 - 27.08.2000
boek